Mechanistic Studies and Mathematical Models for Mycolactone Toxin and Autoinhibitory WASP: Model Mechanisms for Buruli ulcer Initiation and Spread. - Nyarko, Peter Romeo (2016)
A dissertation submitted to the Department of Mathematics, Kwame Nkrumah University of science and technology in partial fulfillment of the requirement for the degree of Doctor of Philosophy in Applied Mathematics, 2015